2015
DOI: 10.1515/ijhp-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Provision in a Swiss Urban Walk-In-Clinic. Is Advanced Nursing Practice a Solution for a New Model in Primary Care? / Gesundheitsversorgung in einer städtischen Walk-In-Praxis in der Schweiz. Ist Advanced Nursing Practice ein neues Modell in der Grundversorgung?

Abstract: Background: Changing demographic and economic factors are producing serious challenges to Switzerland's primary care providers: meeting the population's growing needs will require redevelopment and reorganization. Large-scale community-based care can be expanded via alternative care models, including walk-in-clinics (WIC) stuffed by interdisciplinary teams, with Advanced Practice Nurses (APNs) playing key roles in the treatment of minor complaints. Aims: To reveal the proportion of adult patients within five e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Studies about APNs in Switzerland are sparse, particularly regarding their role in primary care [2]. Kambli et al [23] estimated that 53% of patient consultations in a Swiss urban walk-in clinic could potentially be taken over by APNs and concluded that the APN role would contribute meaningfully to the Swiss health care system. Another study by Steinbrüchel et al [24] examined the views of GPs on potential models of collaboration between doctors and nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies about APNs in Switzerland are sparse, particularly regarding their role in primary care [2]. Kambli et al [23] estimated that 53% of patient consultations in a Swiss urban walk-in clinic could potentially be taken over by APNs and concluded that the APN role would contribute meaningfully to the Swiss health care system. Another study by Steinbrüchel et al [24] examined the views of GPs on potential models of collaboration between doctors and nurses.…”
Section: Introductionmentioning
confidence: 99%
“…The forthcoming shortage of GPs and the aging population in Switzerland will most certainly increase GPs' time burden and negatively affect home visits in the future. Increasing the number of GPs through improved training, better work-life balance and higher financial attractiveness [34][35][36], as well as delegation of home visits to advanced practice nurses [37,38] or private home healthcare agencies [39] are possible options to face the upcoming challenges in primary care in Switzerland.…”
Section: Discussionmentioning
confidence: 99%